2022
DOI: 10.1103/physrevd.105.024046
|View full text |Cite
|
Sign up to set email alerts
|

Ghost of vector fields in compact stars

Abstract: Spontaneous scalarization is a mechanism that allows a scalar field to go undetected in weak gravity environments and yet develop a nontrivial configuration in strongly gravitating systems. At the perturbative level it manifests as a tachyonic instability around spacetimes that solve Einstein's equations. The endpoint of this instability is a nontrivial scalar field configuration that can significantly modify a compact object's structure and can produce observational signatures of the scalar field's presence. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 93 publications
1
29
0
Order By: Relevance
“…Recent work on vectorization, i.e., the spontaneous growth of vector fields in vector-tensor modified gravity models has uncovered ghost type instabilities which occur when there is a change in the signature of the effective metric for the scalar mode of the Proca field [20][21][22]. In such theories, the instability is triggered by non-minimally coupled vector perturbations, and is closely related to the presence of a potential tachyonic mode.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on vectorization, i.e., the spontaneous growth of vector fields in vector-tensor modified gravity models has uncovered ghost type instabilities which occur when there is a change in the signature of the effective metric for the scalar mode of the Proca field [20][21][22]. In such theories, the instability is triggered by non-minimally coupled vector perturbations, and is closely related to the presence of a potential tachyonic mode.…”
Section: Introductionmentioning
confidence: 99%
“…Since the branch of vectorized solutions is disconnected from the GR branch, spontaneous vectorization would not proceed as a continuous evolution from a GR solution. Indeed, in GR solutions the scalar mode suffers from ghost instabilities, rather than tachyonic ones [28,30,31]. A similar problem has also been pointed out for the models of spontaneous spinorization [31].…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, in GR solutions the scalar mode suffers from ghost instabilities, rather than tachyonic ones [28,30,31]. A similar problem has also been pointed out for the models of spontaneous spinorization [31]. One important lesson from such models is that for a successful higher-spin extension of spontaneous scalarization the gravitational theory should, on top of having GR solutions, not contain any extra scalar modes.…”
Section: Introductionmentioning
confidence: 80%
“…Whether this indeed can occur for vector fields is an important issue because a tachyonic destabilization is a possible mechanism to generate compact astrophysical objects with vector hair starting from a hairless initial state-a phenomenon known as vectorization [79][80][81][82]. The no-go result of [38], together with the more general analyses in [83,84], cast doubt on vectorization as a viable mechanism, as they showed that localized perturbations must be either stable or else grow through wrong-sign kinetic or gradient operators. Our present results further supplement this claim by demonstrating that global bound-state solutions on a Schwarzschild BH background likewise do not exhibit tachyonic growth.…”
Section: Discussionmentioning
confidence: 99%